Answer:
![log x-(log(x^(2)+1) )/(2)-tan^(-1) x](https://img.qammunity.org/2021/formulas/mathematics/college/wxrw9cdt7d0933vg0zv7bfbcrhc2em7bt2.png)
Explanation:
step 1:- by using partial fractions
......(1)
step 2:-
solving on both sides
![1-x=A(x^(2) +1)+(Bx+C)x......(2)](https://img.qammunity.org/2021/formulas/mathematics/college/5cm4cek3yb50etmny4dny2i8nvnbt3enp5.png)
substitute x =0 value in equation (2)
1=A(1)+0
A=1
comparing x^2 co-efficient on both sides (in equation 2)
0 = A+B
0 = 1+B
B=-1
comparing x co-efficient on both sides (in equation 2)
-1 = C
step 3:-
substitute A,B,C values in equation (1)
now
![\\\int\limits^ {} \, (1-x)/(x(x^(2)+1) ) d x </p><p>=\int\limits^ {} (1)/(x) d x +\int\limits^ {} (-x)/(x^(2)+1 ) d x -\int\limits (1)/(x^(2)+1 ) d x](https://img.qammunity.org/2021/formulas/mathematics/college/nilbqicxvg0z55fv5pmlf3yxrl15nv7yrb.png)
by using integration formulas
i) by using
.....(b)
.....(c)
step 4:-
by using above integration formulas (a,b,and c)
we get answer is
![log x-(log(x^(2)+1) )/(2)-tan^(-1) x](https://img.qammunity.org/2021/formulas/mathematics/college/wxrw9cdt7d0933vg0zv7bfbcrhc2em7bt2.png)